How does feminization increase equality? The case of lawyers. - Chiu, Charlotte; Leicht, Kevin T. (Law & Society Review, 1999)
Part of a special section on changing employment statuses in the practice of law. A study was conducted to determine whether or not the legal profession can be classed as experiencing successful feminization. Data were drawn from census data from 1970, 1980, and 1990 and from a sample of lawyers surveyed in 1984 and 1990 as part of the National Survey of Lawyers' Career Satisfaction. Findings indicate that the legal profession was on the road to achieving successful gender integration and feminization during the 1980s. Findings demonstrate that overall improvements in the economic position of female attorneys compared with males are happening among women at or below the median in the earnings distribution and among elite lawyers at the top of the earnings distribution.